Kahir - Eivazi, Farhad (Iran, 2015)
Set in Kahir, Iran, this film is about and the perception of women’s bodies in different cultural settings whether religious, social, ideological, economic or personal.
Verzio Film Festival Submission
Keywords: Documentary films